Partnership for impact: EC, IFAD, and CIAT - International Center for Tropical Agriculture (2014)
The European Commission (EC) joined CGIAR in 1977 and is one of the largest multilateral donors and investors, helping set research priorities, contributing scientific expertise and policy advice, and providing financial support. Europe’s strategic investments in CIAT’s research, administered by IFAD, over the years have made significant impact in strengthening food security, protecting natural resources, and fostering inclusive and sustainable economic development for smallholder farmers and rural communities.